The Effect Of Long Time Cooking on the Organoleptic and Chemical Quality of Smoked Patin Fish (Pangasius sp) With Coconut Cook And Corn Cob Sources Combination - Fahrul, Fahrul; Syahrul, Syahrul; Pratiwi, Putri Ayunda; Rahmah, Andi Nur; Maulana, Muhammad Dinar (Fakultas Pertanian, Universitas Muhammadiyah Maluku Utara, 2023)
Then organoleptic test and chemical test were conducted. The results showed that in the 3-hour smoking time, smoked catfish contained 59.54% water content and 2.08% protein content, in the 4-hour smoking time with 56.03% water content and 1.61% protein content, in the 5-hour smoking time with 54.46% water content and 1.47% fat content, in the 6-hour smoking time with 50.91% water content and 1.47% fat content. In the organoleptic test, the appearance of the 3-hour smoking time is 7.53, the smell is 7.76, the taste is 7.64, the texture is 7.18, the appearance of the 4-hour smoking time is 7.29, the smell is 7.64, the taste is 7.46, the texture is 7, 40, the appearance of 5 hours long smoking with a value of 7.22, odor with a value of 7.64, taste with a value of 7.67, texture with a value of 7.91, the appearance of 6 hours long smoking with a value of 7.20, odor with a value of 7.56, taste with a value of 7.80, and texture with a value of 8.09. By using the hot smoking process, the Organoleptic Test of smoked catfish in terms of appearance, odor and taste in all treatments showed no different results, while in terms of the texture of smoked catfish in the 6-hour treatment was the best result. The best water content of smoked catfish is found in the 6-hour treatment and the analysis of fat content in all treatments shows no difference.